Immunogenicity of Oral Polio Vaccine and Salk Inactive Polio Vaccine Against Xinjiang Imported Type 1 Wild Poliovirus - Yan, Dongmei; Wang, Dongyan; Zhu, Shuangli; Zhang, Yong; Li, Xiaolei; Tang, Haishu; Guan, Jing; Xu, Wenbo (Clinical infectious diseases, 2020)
An outbreak of an imported Type 1 wild poliovirus from Pakistan occurred in the Xinjiang Uygur Autonomous Region of China in 2011, although the local immunity status of the oral polio vaccine (OPV) was relatively satisfied. Neutralizing antibody titers against the Xinjiang strain and Sabin 1 strain were measured in 237 sera from 3 groups of fully OPV-vaccinated persons and 1 group of infants fully vaccinated with the inactive polio vaccine (IPV). Additionally, 17 sera collected from 1 Xinjiang poliomyelitis case and his 16 contacts were also tested. Genomic sequencing was conducted the Xinjiang strain. The antibody titers against the Xinjiang strain in each of 237 sera were significantly lower than those against the Sabin 1 strain. Notably, 40.0% of children in Group 1 were seronegative against the Xinjiang strain, which indicated that they might play an important role in wild poliovirus transmission, although their antibody titers against the Sabin 1 strain varied between 1:8 and 1:512. Meanwhile, serological results of the Xinjiang poliomyelitis case and his contacts also provided evidence that a proportion of OPV-vaccinated children had indeed been involved in the transmission chain of the Xinjiang outbreak. Genomic sequencing indicated that the Xinjiang strain was greatly distinguishable from the Sabin 1 strain in neutralizing antigenic sites. The lack of neutralizing antibodies against the Xinjiang strain in persons vaccinated by OPV may be associated with the transmission of Type 1 wild poliovirus in Xinjiang. Using Salk IPV along with OPV might be considered in a wild poliovirus outbreak response, especially in the countries which continued to have persistent wild poliovirus circulation.